ANALISIS CURRENT RATIO, DAN DEBT TO EQUITY RATIO TERHADAP RETURN SAHAM PERUSAHAAN MANUFAKTUR YANG TERDAFTAR PADA BURSA EFEK INDONESIA - B31109091, YUDI MULYONO (Jurnal Manajemen Update, 2014)
This study aims to determine the effect of the Current Ratio (CR) and Debt Equity Ratio (DER) to the Stock Return, either partially or simultaneously in an industrial manufacturing company listed on the Indonesia Stock Exchange between 2009 and 2013. The method of data analysis used is multiple linear regression analysis. Testing statistical hypothesis test is carried out with a simultaneous test (F test) and partial test (t test). The samples were 60 companies listed in Indonesia Stock Exchange. Results of the regression analysis performed after the model was not experiencing classic symptoms such as multicollinearity assumptions, autocorrelation, and heteroscedasticity. F-test of hypothesis testing results show that variable current ratio (CR) and the Debt to Equity Ratio (DER) simultaneously significant effect on stock return. T-test of hypothesis testing results indicate t value for CR was 4,616 compared with 1,668 t of table. While the t value for the DER is -1260 compared with 1,668 t of table. Of both the t value obtained show that the partial effect on CR Stock Return. While partially DER no effect on Stock Return. While the most dominant variable effect on Stock Return is the Current Ratio (CR). Keywords: CR, DER, Stock Return